2016
DOI: 10.1097/aog.0000000000001243
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Swab Test Compared With the Urethral Q-tip Test for Urethral Mobility Measurement

Abstract: Objective To assess whether a vaginal cotton-tipped swab is equivalent to the standard Q-tip test regarding urethral mobility. Secondarily, to examine whether both tests agree in hypermobility diagnosis, discomfort level, and patients' preference. Methods In this randomized cross-over trial, women with stress urinary incontinence without prolapse beyond the hymen were randomized to undergo either a vaginal or urethral mobility test first followed by the alternate approach. The primary outcome was the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The relationship between urethral mobility and stress urinary incontinence has been assessed using a range of techniques, including the POP-Q point Aa descent 69 , urethral Q-tip 70 , vaginal cotton swab 71 , visual evaluation 72 , ultrasonography 72 and lateral chain urethrocystography 73 . However, none of these is recommended and there is no consensus definition for clinically relevant urethral hypermobility.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…The relationship between urethral mobility and stress urinary incontinence has been assessed using a range of techniques, including the POP-Q point Aa descent 69 , urethral Q-tip 70 , vaginal cotton swab 71 , visual evaluation 72 , ultrasonography 72 and lateral chain urethrocystography 73 . However, none of these is recommended and there is no consensus definition for clinically relevant urethral hypermobility.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Meyer et al suggested Valsalva with a cotton swab inserted into the vagina as an alternative to the Q-tip test. The comparison of the VAS scores showed that the patients found the vaginal stick method to be less uncomfortable (27). In clinics where ultrasonography is part of the examination, urethral hypermobility can be easily observed and measured with the change in α angle with Valsalva (R α) instead of the rather uncomfortable Q-tip test.…”
Section: Accurate Evaluation Of the Stress Incontinence Is Of Great I...mentioning
confidence: 99%
“…Because urethral discomfort can occur during Q-tip testing, some authors have tried to substitute it with other surrogates [21][22][23][24]. Meyer et al [21] used a vaginal swab test to predict urethral hypermobility; however, 11 of 80 results (13.8%) were found to be false negatives.…”
Section: Injmentioning
confidence: 99%
“…Because urethral discomfort can occur during Q-tip testing, some authors have tried to substitute it with other surrogates [21][22][23][24]. Meyer et al [21] used a vaginal swab test to predict urethral hypermobility; however, 11 of 80 results (13.8%) were found to be false negatives. Robinson et al [22] used a visual urethral mobility exam to predict urethral hypermobility; however, the visual urethral mobility exam only contains binomial data (i.e., the presence or absence of urethral hypermobility), not continuous data.…”
Section: Injmentioning
confidence: 99%